IMPLEMENTASI KEBIJAKAN PERATURAN BUPATI SIDOARJO NOMOR 62 TAHUN 2018 TENTANG SISTEM PERIZINAN TERINTEGRASI SECARA ELEKTRONIK (ONLINE SINGLE SUBMISSION) PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU(DPMPTSP) KABUPATEN SIDOARJO - Sherina Hanifah, Nanda; Warsono, Hardi; Larasati Setianingsih, Endang (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
The demand for change is often directed at government officials regarding the public services provided. In order to improve public services in Indonesia, a policy is needed that can regulate public services in Indonesia to be more effective. The problem that occurs in public services is that there are many public complaints related to business licensing. According to data from the East Java Ombudsman, DPMPTSP ranks 2nd largest in public reports with a total of 6.43%. The purpose of this study is to identify and analyze the Implementation of the Sidoarjo PERBUP Policy Number 62 of 2018, as well as to identify and analyze the factors that encourage and hinder the implementation of the Electronically Integrated Licensing System Policy (Online Single Submission) Based on the Edward III Model. This research method uses a descriptive research method using a qualitative approach where this study will describe and explain the objects related to the study problem. The results of this study indicate that the implementation of the electronically integrated licensing service policy through OSS, when assessed from the communication factor, is quite good but needs to be improved. The socialization that was held has spread, but it turns out that there are individual business actors who have been missed so that they have not received the information directly from the local government. The implementation of the integrated licensing service policy electronically through OSS, if assessed from the Resource factor, is good, but there are still some things that need to be improved. The existing human resources are quite responsive and most of them already understand the policy, but in fact there are still employees who do not really understand the policy, thus hampering the implementation of the new policy. The budget resources are also quite good with the completeness of the facilities and infrastructure, but need to be improved again because of frequent system errors on the OSS web. The implementation of the integrated licensing service policy electronically through OSS, if assessed from the Disposition factor, is still low. The implementation of the integrated licensing service policy electronically through OSS, if assessed from the Bureaucratic Structure factor, is still low.